Study of demographic determinants of H. pylori infection and the implications on endoscopic findings - Saxena, M. K.; Rana, Rooman Ahmad; Gupta, Ashutosh; Ahmad, Ausaf (International Surgery Journal, 2019)
Background: Helicobacter pylori plays an important role in management of dyspepsia, as well as being a known carcinogenic risk factor. It is ubiquitously present in community to the extent of 50-80% in different studies depending upon the sampling from an urban area or a rural area, as well as socio-economic factors, as also the fact it is a risk factor for carcinoma in elderly age group and Peptic ulcer disease in relatively younger population. The study aimed at studying demographic profile in terms of the age and gender of patients, ascertaining its correlation with H. pylori. Methods: This is a retrospective descriptive study based on the upper GI endoscopies carried out in the institution. The period covered was from 01 January 2018 to 31 December 2018. The inclusion and exclusion criteria were well defined. Statistical analysis was carried out using SPSS Version 16.0 Chi-Square was applied. Results: This is a retrospective descriptive study based on the upper GI endoscopies carried out in the institution. The period covered was from 01 Jan 2018 to 31 Dec 2018. The inclusion and exclusion criteria were well defined. Statistical Analysis was carried out using SPSS Version 16.0 Chi-Square was applied. Conclusions: The study confirms the relationship of age and gender with presence or absence of H. pylori infection.